VALIDITY IN COMPUTER-BASED TESTING: A LITERATURE REVIEW OF COMPARABILITY ISSUES AND EXAMINEE PERSPECTIVES - Ika Kana Trisnawati (Englisia: Journal of Language, Education, and Humanities, 2015)
These past years have seen the growing popularity of the Computer-Based Tests (CBTs) in various disciplines, for various purposes, although the Paper-and Pencil Based Tests (P&Ps) are still in use. However, many question on whether the use of CBTs outperform the effectiveness of the P&Ps or if the CBTs can become a valid measuring tool compared to the PBTs. This paper tries to present the comparison on both the CBTs and the P&Ps and their respective examinee perspectives in order to figure out if doubts should arise to the emergence of the CBTs over the classic P&Ps. Findings showed that the CBTs are advantageous in that they are both efficient (reducing testing time) and effective (maintaining the test reliability) over the P&P versions. Nevertheless, the CBTs still need to have their variables well-designed (e.g., study design, computer algorithm) in order for the scores to be comparable to those in the P&P tests since the score equivalence is one of the validity evidences needed in a CBT.